Barriers to Effective Learning: Examining the Influence of Delayed Feedback on Student Engagement and Problem Solving Skills in Ubiquitous Learning Programming - Fakhri, M. Miftach; Ansari Saleh Ahmar; Rosidah, Rosidah; Fadhilatunisa, Della; Tabash, Mosab (Journal of Applied Science, Engineering, Technology, and Education, 2024)
The rapid evolution of technology has reshaped the educational landscape, ushering in ubiquitous learning environments that provide learners with unparalleled access to educational resources at any time and location. This study aimed to investigate the impact of delayed feedback on student engagement and problem-solving skills in ubiquitous learning programming environments. The purpose was to understand how different forms of student engagement—behavioral, emotional, and cognitive—influence problem-solving abilities and how students perceive and handle delayed feedback. A quantitative method was employed using a cross-sectional survey design. Data were collected from 293 students enrolled in the Department of Informatics and Computer Engineering, Faculty of Engineering, Makassar State University, who had studied web and mobile programming courses. Standardized questionnaires were administered to measure variables. Quantitative data analysis involved descriptive statistical analysis and structural equation modeling (SEM) using SmartPLS 4.0. The research results revealed that behavioral engagement (BE) significantly improves problem-solving skills and helps students better handle delayed feedback. Emotional engagement (EE) has the strongest influence on problem-solving abilities and responses to delayed feedback. Cognitive engagement (CE), while not directly enhancing problem-solving skills, significantly aids in the management of delayed feedback. These findings underscore the importance of fostering behavioral and emotional engagement to enhance problem-solving skills and mitigate the adverse effects of delayed feedback. Strategies such as gamification, real-time collaboration, and immediate feedback mechanisms are essential to improve learning outcomes in ubiquitous learning programming environments.